Santos, Manuela de Alcântara, Antero Ferreira, e Fátima Silva, 2023. Livros de notas de um ourives feirante – José Moreira Pinto de Carvalho (1806-1864). Guimarães: Sociedade Martins Sarmento. 300 pp. ISBN 978-989-8706-17-1 - Alves, Jorge Fernandes (CEM – Cultura, Espaço & Memória, 2024)
.